Penerapan Evaluasi Sumatif dalam Pembelajaran BTQ Kelas III SD Plus Bakti Nusantara 666 Cileunyi - Ulum, Saeful (Darul Yasin Al Sys, 2024)
Summative evaluation alludes to an outline of understudy execution and is expected to be accounted for toward the finish of a program of study. Even though summative assessments do not directly affect learning, they frequently influence decisions that can affect learning for students. Qualitative field research is used in this study. This technique is utilized to make sense of intricate peculiarities by gathering nitty gritty information. Phenomenological research seeks to comprehend the experiences of research subjects as well as phenomena such as behavior, perception, motivation, and so on within the context of particular languages and natural environments. According to the results of the interviews, summative assessment takes place at ASTS and ASAS when all of the learning material has been covered. The summative assessment questions at SD Plus Bakti Nusantara 666 Cile unyi are multiple-choice, true/false, matching, and essay. As to, on the grounds that SD In addition to Bakti Nusantara 666 Cileunyi is a tuition based school, the deterrents confronted rely upon the typical degree of understudy accomplishment. Assuming that understudies can't accomplish the KKM, they will be given remuneration by handling the financing questions gave in the expectation of having the option to accomplish an evaluation as per the predetermined KKM. Summative assessment focuses on reporting at the end of a study program and is connected to the conclusion of student achievement. Although they frequently influence decisions that may affect students' learning, summative assessments do not directly affect learning.